2011
DOI: 10.1038/sc.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic spinal cord injury: an observational study

Abstract: Study design: Retrospective descriptive observational study. Objective: The primary objective of this study was to quantify the incidence of iatrogenic spinal cord injury (SCI) at our SCI unit (SCIU). The secondary objective was to discover the surgical and medical procedures that cause iatrogenic SCI and to estimate the incidence with each procedure. Subjects: Patients admitted to or seen at outpatient services of the SCIU at a university hospital. Methods: Histories were compiled from 1 July 2005 to 30 June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Although this is a separate aetiology in the ISCoS core dataset and is usually reported as a distinct category [22], it was more appropriate in this study to include it with “other” causes for statistical purposes. Iatrogenic injuries (15 cases, 4.3% of total number of TSCI) were less common than those reported in Spain (10–18.2%) but more common than those reported in the previous study of TSCI epidemiology in Ireland (2%) [2, 23, 24]. …”
Section: Discussionmentioning
confidence: 45%
“…Although this is a separate aetiology in the ISCoS core dataset and is usually reported as a distinct category [22], it was more appropriate in this study to include it with “other” causes for statistical purposes. Iatrogenic injuries (15 cases, 4.3% of total number of TSCI) were less common than those reported in Spain (10–18.2%) but more common than those reported in the previous study of TSCI epidemiology in Ireland (2%) [2, 23, 24]. …”
Section: Discussionmentioning
confidence: 45%
“…Previous study suggested that risk of iatrogenic SCI may be related to age [1,2]. In this study, the average age of patients in the research group was 42.48 ± 16.41, which was much elder than 30.05 ± 8.06 of the control group (p < .05), the difference suggested that elder patients would more easily suffer from iatrogenic SCI.…”
Section: Discussionmentioning
confidence: 44%
“…Alcanyis-Alberola et al reported 14.7% (32/250) patients with SCI were caused by iatrogenic mechanisms [1]. Because it results in deterioration of motor, sensory, or autonomie function of the spinal cord involved, iatrogenic SCI lowers patients' quality of life, increases length of stay (LOS) in hospitals, and brings heavy mental and financial burdens to victims and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic spinal cord injury (SCI) is the most devastating complication of spine surgery with the incidence of approximately 0% to 2%, generally less than 1% 3-5. The iatrogenic SCI usually results in chronic pain, loss of sensory and motor function, paralysis, and is even life-threatening 6, 7. The spinal cord is soft, thin, fragile and lies deeply in narrow space, leading to increased operation complexity and ultra-low fault tolerance during spine surgery 1, 2, 8.…”
Section: Introductionmentioning
confidence: 99%